PENGARUH STUDENT COMPANY DAN MINAT BERWIRAUSAHA TERHADAP HASIL BELAJAR ELEMEN PROFESI DAN KEWIRAUSAHAAN - Rodiyah, Siti; Wahyu Dwi Mulyono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyse ‘the effect of Student Company and Entrepreneurial Interest on student learning outcomes in Professional and Entrepreneurship elements at SMKN 5 Surabaya.’ The method applied is quantitative through ex post facto design. The research sample was taken by Purposive Sampling which was composed of 30 class X students majoring in Sanitary Building Construction (KGS) who participated in the Student Company programme. Data collection techniques were carried out through questionnaires to measure Student Company and Entrepreneurial Interest and documentation of Final Semester Examination (UAS) scores as indicators of Learning Outcomes. Then the data is analysed using Simple Regression and Multiple Regression. In the data analysis technique, the results obtained: (1) there is a significant and negative influence between Student Company on the learning outcomes of professional and entrepreneurial elements presented through sig value (0.019) < α (0.05) with a significance level of 5%; (2) there is a significant and negative influence between entrepreneurial interest with learning outcomes of professional and entrepreneurial elements as evidenced through sig value (0.013) < α (0.05) at a significance level of 5%; (3) there is a significant and negative influence between the student company and interest in entrepreneurship simultaneously on the learning outcomes of professional elements and entrepreneurship as evidenced by the sig value (0.043) < α (0.05) at the 5% significance level. The findings of this study indicate that the student company and entrepreneurial interest variables are strong enough to influence student learning outcomes measured by academic scores, so that learning outcome variables measured in the practical domain are needed to strengthen this negative influence theory.